TRADISI NGELEGI MARGA DALAM MASYARAKAT KARO: PROBLEMA IDENTITAS INTEGRASI ATAU MULTIKULTUR (The Tradition of Ngelegi Marga in Karo Society: The Problem of Integrated or Multicultural Identity) - Raharja Sembiring; Rut Debora Butar butar (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
This article aims to describe and to explain the tradition of ngelegi marga in Karo society. It is intended to answer the problem of integrated or multicultural identity due to this tradition. The tradition of ngelegi merga or beru (picking up clans) is a cultural solution for the Karo people to respond to the increasingly complex interactions and expansion of Karo community. This tradition often generates a dilemma between Integration and multiculturalism. The research used in this paper is ethnographic and phenomonological studies, data was obtained through participatory observation, interview and literature study. The tradition of ngelegi merga or trying to embrace all people becomes the subject in the community, so that there is no other subject. The tradition of ngelegi merga or beru does not ignore initial identities but the way of living and establishing relationship within the Karo community. Keywords: Integration, Karo, multicultural, Ngelegi merga or beru.